Formal Methods and Stochastic Models for Performance Evaluation Third European Performance Engineering Workshop, EPEW 2006, Budapest, Hungary, June 21-22, 2006, Proceedings - Horváth, András.; Horváth, András.; Telek, Miklós.; Telek, Miklós. (Programming and Software Engineering ;, 2006)
The idea to establish a European forum for academic and industrial researchers working on various aspects of performance modeling and analysis of manuf- toring and information systems gave rise to an annual series of workshops, - ferred to as European Performance Engineering Workshop (EPEW). The ?rst two EPEW workshops were held in Toledo, Spain, October 1-2, 2004, and V- sailles,France,September 1-3,2005.Thisvolumecontainstheproceedingsofthe third EPEW workshop held at the Technical University of Budapest, Budapest, Hungary, June 21-22, 2006. These proceedings comprise the 16 accepted contributed papers of EPEW 2006.Toensurethehigh-qualityevaluationofthesubmittedpapersweextended the ProgramCommittee of EPEW 2006with international experts from all over the world. Each submitted papers went through a rigorous review by at least three international reviewers. Based on the reviews, the subsequent discussions ofreviewerswithdi?erentjudgementandanInternet-basedProgramCommittee meeting held on March 30, 2006, we selected 40% of the submitted papers. We therefore owe special thanks to all members of the Program Committee and to all external referees for the excellent work they did for the proper evaluation of the papers. The ?nal workshop program, as well as this volume, are made up of ?ve thematic sessions: – Stochastic process algebra – Workloads and benchmarks – Theory of stochastic processes – Formal dependability and performance evaluation – Queues, theory and practice These sessions cover a wide range of performance evaluation methods and c- pose an overview of the current research directions in performance evaluation.